Morgendug og #MeToo: Et møde med en af Henrik Pontoppidans mindre kendte krøniker - Gunder Hansen, Nils (Pontoppidaniana, 2023)
Abstract Morgendug (Morning Dew), one of Henrik Pontoppidan’s early works, is a tale taking place in seemingly realistic set-up but actually containing an important and fascinating “mythical” element. In his article, Nils Gunder Hansen sets out to identify the “anti-romantic powers” on display in the short tale, focusing on the short spells where one of two young men going to market is invited inside a farmer’s house, clearly enchanted by one of the daugthers of the house. Pontoppidan paraphrases a romantic theme of enchantment, suspending time, without clearly specifying the consequences of the event.